Work-related cancer in the European Union: size, impact and options for further prevention - Jongeneel, W.P.; Eysink, P.E.D.; Theodori, D.; Hamberg-van Reenen, Heleen H.; Verhoeven, J.K. (Bilthoven, 2016)
"Despite many protective measures workers can be exposed to carcinogenic substances at work. Additional policy interventions are needed to reduce the future burden of work-related cancer in the EU. The RIVM addressed this issue by providing insight into the magnitude of work-related cancer, in terms of the number of cases, deaths and the societal costs, caused by exposure to carcinogenic substances in the EU. We estimate that in de EU 122,600 (range 91,500 - 150,500) people were newly diagnosed with cancer, caused by past exposure to carcinogenic substances at work. The attributed cancer deaths are estimated to be 79,700 (range 57,700 - 106,500). In total almost 1.2 (0.8 - 1.6) million years of life were lost due to premature death caused by past exposure to carcinogenic substances at work in the EU-population. The consequences of this work-related cancer, and its impact on society, extend further than mortality and morbidity figures. They also include the reduction in the quality of life, productivity losses and the provided health care. Next to the individual emotional suffering and pain associated with the disease, this leads to economic cost for society. Health care expenditure and productivity losses are estimated to cost between ?4-7 billion annually for the EU. When welfare losses of premature deaths and diagnosis with cancer are added, the total annual economic representation of the societal impact is estimated to be in an order of magnitude of ?334 (242 - 440) billion."